قانون جاستا من منظور القانون الدولي - Bzhar Shawkat Kareem (QALAAI ZANIST JOURNAL, 2019)
The event of (September 11) led to the occurrence of new concepts, especially those relating to the sovereignty and immunity of the state. The justa act. Whose bill was approved by parliament, was directed by the president of the United States of America against the right (VETO). The parliament was able to over come its objection, a law was passed ((Justice against sponsors of terrorism act, which it’s passed on 14/July/2016. Under this act the nation court may consider cases in which a litigant is a state or a person who enjoying immunity. Therefore, the researcher examines the concept of the law? The extent of the impact of the international law and international relations? With legal reading of the profusions of the law? And to reflect their consequences in a accordance with international law.